2019
DOI: 10.3390/cryst9110553
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Photostability of Carbamazepine Polymorphs and Cocrystals

Abstract: Carbamazepine (CBZ), a widely used antiepileptic, is known to be sensitive to light. The aim of this study was to evaluate the photostabilities of three cocrystals of CBZ (CBZ-succinic acid (SUC), CBZ-saccharin (SAC) form I, and CBZ-SAC form II) illuminated with a D 65 fluorescent lamp compared with those of the conventional solid forms: CBZ polymorphs (forms I, II, and III). The order of discoloration determined using a colorimetric measurement was almost consistent with that of the degradation rates estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…(1) ). However, a qualitative observation of the overall shape of experimental and RK-calculated traces of such photoreactions indicates that they do not seem to substantially differ from those recorded for reactions subjected to monochromatic light ( Lente and Espenson, 2004 ; Fabian and Lente, 2010 ; Roibu et al, 2018 ; Volfova et al, 2019 ; Yutani et al, 2019 ; Maafi and Al Qarni, 2022a ; Maafi and Al Qarni, 2022b ; Weingartz et al, 2023 ). This observation allows one to conjecture that the kinetics under polychromatic light may well be of -order character, similar to that previously established for the photokinetics of systems exposed to monochromatic light ( Maafi, 2023 ).…”
Section: Resultsmentioning
confidence: 82%
“…(1) ). However, a qualitative observation of the overall shape of experimental and RK-calculated traces of such photoreactions indicates that they do not seem to substantially differ from those recorded for reactions subjected to monochromatic light ( Lente and Espenson, 2004 ; Fabian and Lente, 2010 ; Roibu et al, 2018 ; Volfova et al, 2019 ; Yutani et al, 2019 ; Maafi and Al Qarni, 2022a ; Maafi and Al Qarni, 2022b ; Weingartz et al, 2023 ). This observation allows one to conjecture that the kinetics under polychromatic light may well be of -order character, similar to that previously established for the photokinetics of systems exposed to monochromatic light ( Maafi, 2023 ).…”
Section: Resultsmentioning
confidence: 82%
“…CBZ-NIC and CBZ-SAC co-crystals were prepared by the slow solvent evaporation method according to a previously reported method [22], as shown in Figure 1a. Equimolar APIs (CBZ, 236 mg, 1 mmol) and CFFs (NIC, 122 mg, 1 mmol or SAC, 183 mg, 1 mmol) were dissolved in an amount of ethanol (40 mL) and stirred for 3 h. The solution was slowly evaporated at room temperature and then co-crystals were obtained after several days.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [2] found a novel co-crystal of the potent H2 receptor antagonist famotidine (FMT) with masonic acid, which was stable, and showed higher solubility than the intact crystalline phase. Another essential property of photostability was evaluated in carbamazepine polymorphs (forms I to III) and three co-crystals [3]. Yutani et al fully utilized FT-IR, low-frequency Raman spectroscopy, and solid-state NMR to find that lower molecular mobility is the key to higher photostability.…”
Section: Dear Colleaguesmentioning
confidence: 99%